Differential expression of Shh and BMP signaling in the potential conversion of human adipose tissue stem cells into neuron-like cells in vitro - Cardozo, Alejandra Johana (2010)
The nervous system (NS) has a limited self-repair capability and adult neurogenesis is limited to certain regions of the brain. This generates a great interest in using stem cells to repair the NS. Previous reports have shown the differentiation of adipose tissue-derived mesenchymal stem cells (ASCs) in neuron-like cells when cultures are enriched with growth factors participating in embryonic and adult neurogenesis. Therefore, it could be thought that there exists a functional parallelism between neurogenesis and neuronal differentiation of ASCs. For this reason, the goal of this work was to study the differential gene expression of Shh and BMP genetic pathways involved in cell fate determination and proliferation. In this study we demonstrated that hASCs are endowed with active Hedgehog and BMP signaling pathways through the expression of genes of both cascades and that their expressions are downregulated after neuronal induction. This idea is in accordance with the facts that Shh and BMP signaling is involved in the maintenance of cells with stem cells properties and that proliferation decreases during the process of differentiation. Furthermore, Noggin expression was detected in induced hASCs whereas there was no expression in noninduced cells, which indicates that these cells are probably adopting a neuronal fate because noggin diverts neural stem cells from glial to neuronal fate. We also detected FM1-43 and synaptophisin staining, which is evidence of the presence of putative functional presynaptic terminals, a neuron-specific property. These results could partially contribute to the elucidation of the molecular mechanisms involved in neuronal differentiation of adult human nonneural tissues.